Peran BK Mengatasi Persepsi Buruk Siswa terhadap Layanan Bimbingan Konseling - Setiorini, Faradina (Maliki Interdisciplinary Journal, 2024)
Guidance and counseling teachers have a very important role in coordinating guidance and counseling activities in schools. However, guidance and counseling teachers are often underestimated and there is a negative stigma that can hinder the implementation of guidance and counseling programs in schools. This article aims to detail the roles and functions of guidance and counseling teachers, overcome negative perceptions of guidance and counseling programs, and ensure optimal utilization of facilities provided by guidance and counseling to support student learning success. The research method applied is library research, with data collection through archiving techniques and content analysis. The results of the analysis revealed that guidance and counseling teachers have four main functions, namely understanding, prevention, alleviation and maintenance and development. In addition, there is also a distribution and adjustment function. However, even with the existing functions, there are still bad perceptions embedded in students’ minds towards guidance and counseling programs, such as considering counselors as school police or just advice givers. Therefore, this article will provide a comprehensive overview of guidance and counseling teachers in increasing the effectiveness of guidance and counseling programs in schools with the hope of being able to change students’ perspectives on guidance and counseling programs to be more positive.